Ujian Praktikum Histologi dengan Tayangan Foto Menghasilkan Skor yang Lebih Tinggi - Rina Susilowati; Jajah Fachiroh; Andwi Ari Sumiwi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2016)
Background: Since 2003, Histology practical session in Faculty of Medicine Universitas Gadjah Mada as well as its assessment had been subjected into several changes, i.e. methods of practical asessment and the usage of practical session score as block score components. Score of practical session assessments has been used as marker of student’s achievement in mastering the learning objectives. This study compared practical session score of Histology practical assessment between student from batch 2003-2006, 2007-2010 and 2011-2012, in order to determine which method give highest student achievement.Method: Score of histology practical assessment from 3 groups of medical students were obtained from the archive. The data was reported as mean±SD and number distribution of the students with score ≥60. The difference between groups was analyzed using t-test and chi-square. Results: There were 2213 students included in this study, i.e. 735 of year 2003-2006 (microscope-based test, score used as component of block score), 920 of year 2007-2010 (microscope-based test, score not used as component of block score), and 558 of year 2011-2012 (micrograph-based test, score was used as component of block score). Mean score for each group were 76,83±7,40; 74,54±14,40; dan 83,47±9,02, respectively. Percentage of students with score ≥60 were 83,59%, 73%, dan 97,49%. There were significant difference between groups (P<0.0001). Conclusion: Score of histology practical assessment was higher in students tested with micrographs visualized by projector. The percentage of students with score ≥60 was higher when the score was used as component of block score.